Get detailed and accurate responses to your questions on IDNLearn.com. Get accurate and detailed answers to your questions from our knowledgeable and dedicated community members.
Sagot :
To convert the given equation [tex]\( y = x + 5 \)[/tex] into Standard Form, we need to express it in the form [tex]\( Ax + By = C \)[/tex], where [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex] are integers, and [tex]\( A \)[/tex] should be a non-negative integer.
1. Start with the given equation:
[tex]\[ y = x + 5 \][/tex]
2. Subtract [tex]\( x \)[/tex] from both sides to move [tex]\( x \)[/tex] to the left side of the equation:
[tex]\[ y - x = 5 \][/tex]
3. For the standard form, we generally prefer the [tex]\( x \)[/tex]-term to come first and to have a positive coefficient. If needed, we multiply the entire equation by -1 to achieve this. In this case:
[tex]\[ -x + y = -5 \][/tex]
4. Rearrange the terms to achieve the Standard Form [tex]\( Ax + By = C \)[/tex]:
[tex]\[ x - y = -5 \][/tex]
Thus, the equation in Standard Form is:
[tex]\[ \boxed{x-y=-5} \][/tex]
1. Start with the given equation:
[tex]\[ y = x + 5 \][/tex]
2. Subtract [tex]\( x \)[/tex] from both sides to move [tex]\( x \)[/tex] to the left side of the equation:
[tex]\[ y - x = 5 \][/tex]
3. For the standard form, we generally prefer the [tex]\( x \)[/tex]-term to come first and to have a positive coefficient. If needed, we multiply the entire equation by -1 to achieve this. In this case:
[tex]\[ -x + y = -5 \][/tex]
4. Rearrange the terms to achieve the Standard Form [tex]\( Ax + By = C \)[/tex]:
[tex]\[ x - y = -5 \][/tex]
Thus, the equation in Standard Form is:
[tex]\[ \boxed{x-y=-5} \][/tex]
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Thank you for choosing IDNLearn.com. We’re here to provide reliable answers, so please visit us again for more solutions.